2018
DOI: 10.1016/j.jjcc.2017.09.010
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between optical coherence tomography-derived morphological criteria and functional relevance as determined by fractional flow reserve

Abstract: Information on OCT-derived LVI and lesion locations facilitates better identification of coronary lesions that cause ischemia than OCT-derived MLA analysis alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although morphological characteristics of plaques, such as lipid arc and lipid length assessed by OCT presented a significant correlation with FFR in studies by Usui et al and Lee et al [21,27], no independent association with FFR in the model including OCT-derived MLA could be demonstrated. The present study also builds up on the recently pub-…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although morphological characteristics of plaques, such as lipid arc and lipid length assessed by OCT presented a significant correlation with FFR in studies by Usui et al and Lee et al [21,27], no independent association with FFR in the model including OCT-derived MLA could be demonstrated. The present study also builds up on the recently pub-…”
Section: Discussionmentioning
confidence: 77%
“…Although morphological characteristics of plaques, such as lipid arc and lipid length assessed by OCT presented a significant correlation with FFR in studies by Usui et al and Lee et al [21,27], no independent association with FFR in the model including OCT-derived MLA could be demonstrated. The present study also builds up on the recently published results from a smaller study by Burzotta et al who, amongst 45 patients with CAD, found that a combination of different OCT parameters, such as MLA, % area stenosis, presence of thrombus or plaque ulceration could aid in prediction of significant FFR results [4].…”
mentioning
confidence: 77%
“…There is a wide range of OCT parameters values which can have a strong correlation with hemodynamic significance of a coronary lesion, but this values depend on the cut-off chosen for the differentiation of ischemic and non-ischemic lesions [11,15,17]. While for a cut-off value of 0,75 a much lower threshold for MLA was obtained in other studies [11], for the present analysis the FFR cut-off was chosen to be 0,80 for the purpose of being in line with the majority of studies addressing the same parameters. According to our results, a MLA derived from OCT has a good correlation with a FFR value under 0,80.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the correlation between minimal luminal area (MLA) measured by OCT and FFR in patients with coronary artery disease for patients with chronic coronary syndromes [10][11][12] . The aim of the studies was to establish a relationship between the anatomical and physiological assessments of coronary lesions in patients with acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…OCT examination was performed using frequency-domain OCT systems: Abbott’s OCT (Ilumien Optis, Abbott Vascular, Santa Clara, CA, USA) or Terumo’s optical frequency-domain imaging system (Lunawave, Terumo Corporation, Tokyo, Japan), as previously described [ 12 , 13 ]. OCT pullback was performed automatically by the dedicated device during the injection of flushing agents, either contrast medium or low-molecular-weight dextran with Ringer’s lactate solution, at a flow rate of 3–4 mL/s via the guiding catheter using an automated power injector pump.…”
Section: Methodsmentioning
confidence: 99%